Charlotte's web, - White, E. B. (Elwyn Brooks), 1899- (Harper & Row, 1952)
Wilbur, the pig, is desolate when he discovers that he is destined to be the farmer's Christmas dinner until his spider friend, Charlotte, decides to help him.